Pengaruh Rebusan Jahe Merah untuk Mengurangi Nyeri Haid pada Mahasiswi Diploma Tiga Keperawatan Universitas Abulyatama - Herni Murnaliyanti Munte; Urip Pratama; Mansuriza, Mansuriza (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Menstrual pain is one of the most common health complaints experienced by many women and often interferes with daily activities, both in academic and social contexts. This study aimed to examine the effect of red ginger decoction in relieving menstrual discomfort. The research employed a quasi-experimental design with a One Group Pretest-Posttest approach. From a total population of 487 students enrolled in the Diploma III Nursing program, 15 participants were selected using purposive random sampling. The study was conducted over a three-week period, from May 7 to May 27, 2025, using an observation sheet as the research instrument. The initial pain level was measured before the intervention using the Numeric Rating Scale (NRS). Each participant who reported menstrual pain was then given 200 ml of red ginger decoction, and after 30 minutes, pain levels were reassessed to determine any changes. The Shapiro-Wilk test was applied to examine data distribution, while differences in mean scores before and after the intervention were analyzed using the Paired Sample t-Test. The findings showed that the average pain score before treatment was 7.53 and decreased to 5.67 after the intervention, with a mean difference of 1.89. The statistical analysis yielded a significance value of p = 0.001 (p < 0.05), indicating a meaningful difference. Therefore, it can be concluded that consuming red ginger decoction is effective in reducing menstrual pain intensity. Consequently, red ginger may be recommended as a natural alternative for managing dysmenorrhea, while educational institutions are encouraged to provide health education regarding the use of herbal remedies, particularly red ginger, for menstrual pain relief. Future researchers are expected to use these findings as a reference and further explore other variables in subsequent studie.